Prevention Adaptation of an Evidence-Based Treatment for Parents Involved With Child Welfare Who Use Substances - Cruden, Gracelyn; Crawford, Shelley; Saldana, Lisa (Frontiers in Psychology, 2021)
Background: Parental substance use, especially opioid misuse and/or methamphetamine use, is a key driver for recent increases in family involvement with child welfare and foster care placements in the United States. There is an urgent need for programs that prevent parental substance use disorders, yet few prevention programs exist that target parents’ unique needs and strengths. Adapting evidence-based treatment approaches for prevention might be an efficient, effective way to address this gap. The current study informed the rigorous adaptation of an evidence-based treatment that supports families involved with child welfare due to substance use, Families Actively Improving Relationships (FAIR), to a prevention-oriented intervention: “PRE-FAIR.” FAIR entails four treatment domains: substance use, parenting, mental health, and ancillary services (e.g., housing, medical care, food). FAIR significantly improved parenting and reduced parental substance use in three rigorous treatment trials, but FAIR’s effectiveness in preventing the initiation or escalation of opioid misuse and/or methamphetamine use is untested. To inform adaptation, particular attention was paid to operationalizing strategies underlying a key hypothesized mediator of successful parent outcomes—engagement. Methods: Graduated FAIR parents (n = 9) and FAIR administrators, clinical supervisors, and clinicians (n = 11) participated in semi-structured interviews. Content analysis was used to identify key variables driving FAIR engagement and parent outcomes. Causal loop diagramming, a qualitative systems science method, was employed to operationalize emergent themes and describe how causal links between key variables interrelated dynamically over time. Results: Themes reinforced the value of FAIR’s treatment domains for supporting parent’s sobriety and parenting skills within a prevention orientation. Ancillary supports and strong relationships were particularly crucial for helping parents cope with stressors leading to substance use. Five engagement strategies were identified as essential to parent success: 24/7 clinician availability, in-person clinician advocacy, in-home delivery, strengths-based interactions, and urinalysis. Implications for PRE-FAIR engagement strategies and dosage were identified. Discussion: Traditional qualitative analyses and qualitative analyses based in systems science can inform rigorous adaptations of evidence-based treatment programs for prevention. Future research will explore additional required, fidelity-consistent prevention adaptations to FAIR, and the impact of PRE-FAIR on parental substance use and child welfare case outcomes.